Current regional climate of the Antarctic Peninsula and Akademik Vernadsky Station - V. F. Martazinova; V. E. Tymofeyev; Ye. K. Ivanova (Ukrainian Antarctic Journal, 2010)
This article presents the current state of the climate regime of the Antarctic Peninsula region. Characteristic of regional warming and reasons for the formation of extreme weather events are studied by means of long-term changes in near-surface air temperature on the Ukrainian Antarctic Vernadsky station, as well as other stations with long-term uninterrupted series. Regime of precipitation and surface wind at Vernadsky station is also studied.